Semantic Dementia without Surface Dyslexia in Spanish: Unimpaired Reading with Impaired Semantics - Wilson, Maximiliano A. (Behav Neurol, 2012)
Surface dyslexia has been attributed to an overreliance on the sub-lexical route for reading. Typically, surface dyslexic patients commit regularisation errors when reading irregular words. Also, semantic dementia has often been associated with surface dyslexia, leading to some explanations of the reading impairment that stress the role of semantics in irregular word reading. Nevertheless, some patients have been reported with unimpaired ability to read irregular words, even though they show severe comprehension impairment. We present the case of M.B., the first Spanish-speaking semantic dementia patient to be reported who shows unimpaired reading of non-words, regular words, and–most strikingly–irregular loan words. M.B. has severely impaired comprehension of the same words he reads correctly (whether regular or irregular). We argue that M.B.’s pattern of performance shows that irregular words can be correctly read even with impaired semantic knowledge corresponding to those words.